Self-Enhancement in Latin America: Is It Linked to Interdependence? - Salvador, Cristina E.; Idrovo Carlier, Sandra; Ishii, Keiko; Castillo Torres, Carolina; Nanakdewa, Kevin; Canale Segovia, Fernanda; San Martin, Alvaro; Savani, Krishna; Kitayama, Shinobu (SAGE Publications Inc., 2025)
Although individuals of Latin American heritage ( Latin Americans in short) are considered interdependent, they also value traits like uniqueness and positivity, like individuals of European American cultural heritage, who are considered independent. It remains unclear whether this inclination toward positivity extends to a bias in self-perception known as self-enhancement. Moreover, if Latin Americans are indeed self-enhancing, it is uncertain how these tendencies align with their interdependent cultural orientation. In this article, we report three studies ( N = 1,246) with three operationalizations of self-enhancement. We found that Mexicans, Colombians, and Ecuadorians show self-enhancement that is mostly similar in magnitude to European Americans. Notably, Study 3 found that self-enhancement is related to interdependence in Latin America: Unlike European Americans, Latin Americans in Ecuador exhibited stronger self-enhancement when interdependence is primed rather than independence. Our findings suggest that among Latin American individuals, self-enhancement not only exists but also reinforces interdependence. ©The authors ©Personality and Social Psychology Bulletin
Keywords: Culture; Self; Self-enhancement; Self-evaluation; Latin America